An Evaluation of the Management of Floresta Nacional do Tapajós, Belterra-Pa, in the Perception of the Residents of Maguari Community (Revista Brasileira Multidisciplinar, 2014)
The present research proposed to assess the management adopted on TNF in the city of Belterra-PA according to the perception of the residents. With this aim, an exploratory research was developed, consisted, initially, of a literature review on the topic followed by a field research, using as data collection instrument the application of 146 questionnaires/interviews to Maguari community residents. One of the residents interviewed, 85% Maguari community claim, from a personal standpoint, that the management of the Flona Tapajos is efficient and 76% believe that the local population is under this management. The degree of adoption of effective management in the TNF, 51% said it was good. The majority of respondents (92%) recognizes that there are limits regarding use of natural resources within the Maguari Community. The residents feel the need of professional qualification courses, they are more informed about what happens in relation to the Tnf and, mainly, which involves the Maguari Community. The interventions performed on the TNF occur through numerous projects and programs directed to the change in the behavior of Maguari community residents regarding the preservation and conservation of the environment, but the management model adopted by the Tapajós national forest still leaves something to be desired, according to the perception of the residents of the community, even in the presence of a management plan.
Keywords: Conservation unit; FLONA- Tapajos; Environmental management.